Statement on the Article of the Year 2021: "The Influence of Differential Peer Associations on Delinquency Varies Depending on the Combination of Unstructured Socializing and Personal Morals" von Florian Kaiser (Kriminologie - Das Online-Journal | Criminology - The Online Journal, 2022)
Laudatio Beitrag des Jahres